Exploring gen Z’s green purchase intentions for sustainable products - Mirah, Gusti Ayu; Martini, I.A. Oka (International Journal of Financial, Accounting, and Management, 2025)
Purpose: This study aims to analyse the role of environmental concern and green perceived value in mediating the effect of environmental strategy on green purchase intention, particularly in the beauty industry. Research methodology: This research is located in Bali using The Body Shop brand. The population consists of consumers living in Bali who have never purchased green products from The Body Shop. A total of 160 respondents were selected using purposive sampling. Data were analysed using inferential statistical analysis with SEM based on partial least square (PLS). Results: The study shows that environmental strategy has a direct, positive, and significant effect on green purchase intention, environmental concern, and green perceived value. Green perceived value significantly affects green purchase intention, while environmental concern does not. However, both environmental concern and green perceived value significantly mediate the indirect relationship between environmental strategy and green purchase intention. Conclusions: Environmental strategy influences green purchase intention both directly and through perceived value and concern. While green perceived value enhances intention, high environmental concern may reduce it, reflecting Gen Z’s skepticism toward sustainability claims. Limitations: The study is limited to 160 Generation Z respondents, so the findings may not be generalised to other generational groups or larger populations. Contribution: This study contributes to expanding knowledge and developing academic understanding of the theoretical factors influencing green purchase intention.